2017
DOI: 10.1111/vcp.12446
|View full text |Cite
|
Sign up to set email alerts
|

Cell tube block: a new technique to produce cell blocks from fluid cytology samples

Abstract: The CTB method was easily implementable under practice conditions (up to the fixation of the microhemtocrit tube), analogous to surgical biopsy submission for histology. Cell tube blocks can increase diagnostic accuracy when the technique is used in tandem after the cytologic evaluation, and the technique allows storage of fluids. Other advantages of CTB were the simplicity, low cost, and separation of erythrocytes from the nucleated cells, which was helpful in hemodiluted samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 11 publications
1
55
0
Order By: Relevance
“…In this study, we applied the CTB technique for the first time to study the distribution of cells in the buffy coat of birds and reptiles, and to document pathological conditions, such as hemoparasite infection and IBD (showing that inclusions could be detected). Techniques used to study blood cells in optical and electron microscopy have been described in mammals and prove useful in diagnosing and characterizing the pathologic conditions of chronic lymphocytic leukemia, leukemic dissemination of multiple myeloma, and hemoparasites in the dog . However, it was unknown if such techniques could be applied to animals with nucleated erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we applied the CTB technique for the first time to study the distribution of cells in the buffy coat of birds and reptiles, and to document pathological conditions, such as hemoparasite infection and IBD (showing that inclusions could be detected). Techniques used to study blood cells in optical and electron microscopy have been described in mammals and prove useful in diagnosing and characterizing the pathologic conditions of chronic lymphocytic leukemia, leukemic dissemination of multiple myeloma, and hemoparasites in the dog . However, it was unknown if such techniques could be applied to animals with nucleated erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical and immunohistochemical procedures could be easily applied to CTBs. Therefore, we propose that the CTB technique should be used in pathologic cases, such as in the diagnosis of leukemic dissemination or when atypical cells are present in the blood smear . As to electron microscopy processing, we used a protocol similar to that published for dogs and cats, but simpler than that previously reported for reptiles, such as the Bobtail lizard or Yellow‐Bellied Slider Turtle .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proposed advantages of the CB as documented in human studies include: (a) the preservation of tissue architecture, (b) sample archivability owing to paraffin embedding, (c) the suitability of samples for cytochemical and immunohistochemical staining, (d) a reduced need for excisional biopsy and (e) advantages in the detection of certain malignancies, including lymphoma . Limited studies on the CB or CB‐like techniques in veterinary medicine have demonstrated its utility in the evaluation of lymphoid tissues and in the detection of fungal osteomyelitis, leishmaniasis, mesothelioma and bone marrow carcinoma micrometastasis . While all veterinary publications describing the CB testify to its ease of use, only one has evaluated its utility in the evaluation of the canine reactive and lymphomatous lymph node and in the diagnosis of lymphoma.…”
Section: Introductionmentioning
confidence: 99%